Pemikiran dan Gerakan Dakwah KH. Dja’far Addari - Rusydi Sulaiman (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
The existence of Islam and its varieties among society indicates a big contribution of some scholars including Moslem scholars in Indonesia. KH. Dja’far Addari was one of the pioneers in Bangka who could prove it.—had a big role in changing civilization. Beside idealism and strong struggle, his charisma plays a big role. Dja’far Addari was not only muballigh (conventional Islamic preacher), but productive writer. He travelled far for seek of knowledge (from Bangka Selatan to Mecca) when he was 14 years old under the supervision of salaf Moslem scholars, then went home to his motherland. This article focusses on the thought of Dja’far Addari which consist of Tauhid, syari’ah and Akhlak, then his social movement as Dakwah Islam. Many key persons have been interviewed in searching detail sources in this research. The existence of this Guru implicates some influences, such as: adat istiadat and local tradition, system of belief, strengthening economy and entrepreneurship. The figurism of Dja’far Addari inspires new civilization in Bangka Selatan; Dallas, Airgegas even Pangkalpinang.